Extended‐Spectrum Β‐Lactamase and Plasmid‐Mediated AMPC Genes in Swine and Ground Pork. Issue 1 (8th April 2016) - Sabia, Carla; Stefani, Sara; Messi, Patrizia; de Niederhäusern, Simona; Bondi, Moreno; Condò, Carla; Iseppi, Ramona; Anacarso, Immacolata
Abstract: We investigated the presence of ESBL and AmpC‐producing Enterobacteriaceae isolated from 200 rectal swabs of healthy swine and 200 samples of ground pork. Phenotypic testing by using the double synergy differential test (DSDT) for ESBL/AmpC‐positive strains was confirmed by PCR and DNA sequence analysis. The localization of beta‐lactamase genes was established by conjugation experiments. ESBL and/or AmpC‐producing Enterobacteriaceae was found in 52.2% (95/182) of the isolates collected from rectal swabs and 3% (3/100) of isolates obtained from ground pork samples. Polymerase chain reaction and sequencing confirmed the presence of bla TEM‐20, bla TEM‐34, bla TEM‐52, bla CTX‐M‐1, bla SHV‐12, bla TEM‐1 + SHV‐12, bla TEM‐20 + SHV‐12, bla CMY‐2, bla TEM‐1+ CMY‐2, bla ACC‐1 and bla ACC‐2 . The conjugation assays yielded positive results, denoting a plasmid localization of the genes. Practical Applications: In this study, the prevalence of ESBL and AmpC‐producing Enterobacteriaceae isolated from rectal swabs of healthy swine and samples of ground pork were determined. ESBL/AmpC‐positive strains were confirmed by PCR and DNA sequence analysis. The most frequently isolated species was E.coli, among the most common variants detected TEM‐type ESBL, TEM‐52 was showed. These findings provide new information about the presence of ESBL/AmpC at the farm level and have important implications for assessments of risks of meat contamination during slaughter.